Language Politeness in the Batak Toba Community in Jambi City - Sinaga, Maria Br; Purba, Andiopenta; Putra, Yoga Mestika (Journal of Social Science Utilizing Technology, 2024)
Background. Humans as social creatures use language to interact with each other. In the interaction process, language can be spoken and written. Spoken language is expressed in direct speech, while written language is expressed in written form. The Toba Batak people have local wisdom in the form of expressions, namely Pantun hangoluan, tois hamagoan. This means that if we live our lives with polite and courteous behavior, we will have a good life. Purpose. This research aims to determine language politeness in the Toba Batak community in Jambi City. Method. The method used in this research is a qualitative descriptive method. The data source for this research is Toba Batak speakers in Arisan Marga, Parsahutaon, Martandang, and Lapo. Data collection techniques in this research used listening and note-taking techniques. The listening technique is carried out by listening and recording the speech, then the note-taking technique is by recording important data from the informant's speech. The data analysis technique uses the Miles and Huberman method, namely data reduction, data presentation, and drawing conclusions/verification. Results. The results of this research found 94 data that complied with the principles of language politeness maxims. In Arisan Marga there are 29 data, in Parsahutaon there are 22 data, in Martandang there are 19 data, and in Lapo there are 24 data. Compliance with language politeness is mostly dominated by the maxim of wisdom with 39 data, the maxim of agreement with 17 data, the maxim of respect with 16 data, the maxim of generosity with 14 data, the maxim of sympathy with 6 data, and the maxim of humility with 2 data. Conclusion. From the research results it can be concluded that there are more maxims of wisdom than the maxims of humility and the maxims of sympathy.